Acute Tuberculous Appendicitis, a Rare Entity - Gentile, João Kleber de Almeida; Renesto, Beatriz Terezinha Franco; Miléo, Luis Fernando Alves; Oliveira, André Cosme; Horta, Sérgio Henrique Couto; Magella, Flávia; Souza-Filho, Ronaldo Modesto de (Brazilian Journal of Case Reports, 2024)
Tuberculous appendicitis is a rare disease, with an overall incidence of between 1.5-3.0% among tuberculosis patients. It was first described by Corbin et al in 1873 and since then has been rarely recorded in publications and case reports. In the USA, extrapulmonary disease is seen in around 20-30% of tuberculosis patients, with the most common extrapulmonary manifestations being bone (30%), urinary tract (24%) and lymph node (13%) involvement. A high index of suspicion is required to make the diagnosis of appendicular tuberculosis, although it can cause damage to the appendix without other signs of localized disease. We report a case of a woman diagnosed with primary tuberculous appendicitis in a patient with human immunodeficiency virus (HIV), with evidence of extra-intestinal disease.